Causes of delayed diagnosis in patients with colorectal cancer (A Prospective study) - Sulaiman, Tharwat I; Dweni, Aoss H.; Baker, Kassim (Journal of the Faculty of Medicine Baghdad, 2006)
Back ground: Colorectal cancer is one of the leading causes of death allover the world especially in the developed countries. Each year approximately one million veterans aged 50 and older will develop colorectal cancer over the remainder of their lives and nearly 433,000 will die from it. Because most cancers are diagnosed after local or regional spread, nearly half of all patients diagnosed with colorectal cancer will die lWarly detection and management definitely decrease mortality. Patient and methods: This is a prospective study on fifty patients with colorectal cancer admitted at the first surgical unit in Baghdad teaching hospital since March 2000 till March 2003 The data collected from those fifty patients were analyzed according to the history, physical examination and investigations with special consideration to the mode of presentation , type of investigations and the cause of delay in diagnosis, Results: The most valuable investigation was colonoscopy and biopsy Abdominal ultrasound was very helpful tool in diagnosis of right sided colonic tumors.Also barium enema has a good role in diagnosis of patients with colorectal cancer. Conclusion: We concluded that most delay in diagnosis of patients with colorectal cancer was patient related (fifty percent of cases ).A significant delay was related to the patients and general practitioner In a few cases the delay was related to the patients and consultant surgeon and a single case related to the general practitioner only.